2005
DOI: 10.1002/ejlt.200501196
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant behaviour of products resulting from beef sarcoplasmic proteins‐malondialdehyde reaction

Abstract: The antioxidant properties of the soluble fraction of a Maillard reaction product (MRP) model generated from sarcoplasmic protein/malondialdehyde (MDA) were evaluated. The dry extract colour values showed that it has a pale brown colour appearance, and the carbonyl content of isolated protein increased from 2474 nmol/mg protein to 3904 nmol/mg protein, before and after reaction with MDA, respectively. Reducing power (82.34%) and 1,1-diphenyl-2-picryl hydrazyl radical scavenging (35.20%) were very good, while s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The secondary oxidation products of lipid oxidation were measured as TBARS (thiobarbituric acid reactive substances) by spectrophotometric method described by Romero et al (2005) [29]. TBARS were expressed as mg of malondialdehyde (MDA) per kg of fat in samples using 1, 1, 3, 3-tetramethoxypropane (TEP) as a standard.…”
Section: Evaluation Of Oxidative Stability Of Optimized Burgermentioning
confidence: 99%
“…The secondary oxidation products of lipid oxidation were measured as TBARS (thiobarbituric acid reactive substances) by spectrophotometric method described by Romero et al (2005) [29]. TBARS were expressed as mg of malondialdehyde (MDA) per kg of fat in samples using 1, 1, 3, 3-tetramethoxypropane (TEP) as a standard.…”
Section: Evaluation Of Oxidative Stability Of Optimized Burgermentioning
confidence: 99%
“…Requena et al developed an analytical method for the analysis of lysine-malondialdehyde adducts and proved them to be useful biomarkers of lipid peroxidative protein modification and of oxidative stress in vivo and in vitro (9). Investigations of the antioxidant activity of the soluble reaction products of beef sarcoplasmic proteins with malondialdehyde showed that light brown pigments were produced with antioxidant properties, in analogy with nonenzymatic browning (10).…”
Section: Introductionmentioning
confidence: 99%